The Effectiveness of Brain Gym on Concentration and Memory Performance of IT Academic Probation Students: A Case Study of UTAS-Shinas, Sultanate of Oman - Al-Kalbani, Salama Said Sulaiyam; Al Mamari, Bushra Said Obaid; Villar, Redjie Tan (International Journal of Asian Education, 2025)
Despite the various academic services in place, many students still enter academic probation status and find it difficult to exit due to a low Cumulative Grade Point Average (CGPA). High academic achievements require a satisfactory level of concentration and working memory performance. This study aims to examine the effectiveness of Brain Gym exercises in improving concentration and memory levels among students on academic probation. This quasi-experimental study involved 48 students from the College of Computing and Information Sciences at the University of Technology and Applied Sciences (UTAS-Shinas), all in their first-year Diploma semester 1 of the academic year 2024-2025. The participants were allocated into a control group and an intervention group, and both groups were subjected to pre-tests and post-tests. Data on concentration were collected using Grid Concentration Exercise questionnaires, while the Digit Span Test and Spatial Test were used to assess memory performance. Two non-parametric tests were used to analyze the data: the Spearman Rank Order correlation test was used to determine the relationship between the pre-test and post-test scores for both groups, and the Wilcoxon Pair Signed Rank Test was used to measure the difference between the post-test scores of the control and intervention groups. The study's findings show a significant increase in the students’ concentration performance for the intervention group by 19.1%. The finding also shows a significant improvement for Digit Span memory and Spatial Memory Skills among participants in the intervention group by 29.7%.